Antibacterial Activity of Metal Complexes of Cu(II) and Ni(II) with the Ligand 2-(Phenylsubstituted) Benzimidazole - Ivone Vanessa Mañozca-Dosman; Alberto Aragón-Muriel; Dorian Polo-Cerón (Scientia Pharmaceutica, 2025)
Benzimidazoles are considered a promising class of bioactive heterocyclic compounds that show a wide variety of useful biological properties due to their structural similarities to nucleotides such as purines. Among these properties, great attention has been given to the antibacterial activity exhibited by molecules containing a benzimidazole nucleus in their structure since recent research results have shown the potential of such molecules as alternatives in the fight against bacterial resistance. When these compounds have phenylsubstituted groups in the 2-position of the imidazole ring, a series of molecules can be obtained with generally improved pharmacological activity. These types of compounds are suitable for the formation of stable complexes with several transition metals, including nickel and copper; such compounds have also exhibited many biological properties in different reports. Accordingly, this brief review focuses on recent work on the synthesis and characterization of metal complexes of Ni(II) and Cu(II) with ligands derived from 2-(phenylsubstituted) benzimidazole that were subsequently evaluated for antibacterial activity.